2017
DOI: 10.1002/anie.201708748
|View full text |Cite
|
Sign up to set email alerts
|

MoB/g‐C3N4 Interface Materials as a Schottky Catalyst to Boost Hydrogen Evolution

Abstract: Proton adsorption on metallic catalysts is a prerequisite for efficient hydrogen evolution reaction (HER). However, tuning proton adsorption without perturbing metallicity remains a challenge. A Schottky catalyst based on metal-semiconductor junction principles is presented. With metallic MoB, the introduction of n-type semiconductive g-C N induces a vigorous charge transfer across the MoB/g-C N Schottky junction, and increases the local electron density in MoB surface, confirmed by multiple spectroscopic tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
175
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(190 citation statements)
references
References 49 publications
6
175
0
9
Order By: Relevance
“…DFT calculations are applied to demonstrate the catalytic activity after doping from the electronic properties of intermediates and the overall energetic pathway. [37] ThePDOSs benchmark analysis has been also carried out. TheC o-NiS 2 NSs surface shows highly selective to activating the free H 2 Om olecule and oxidizing the adsorbing H 2 Ot hrough as trong coupling with the O-2 pp electrons.T he adsorbed OH species denotes ametallic feature and efficient electron transfer for easily deattaching from the surface (Figure 5b).…”
Section: Resultsmentioning
confidence: 99%
“…DFT calculations are applied to demonstrate the catalytic activity after doping from the electronic properties of intermediates and the overall energetic pathway. [37] ThePDOSs benchmark analysis has been also carried out. TheC o-NiS 2 NSs surface shows highly selective to activating the free H 2 Om olecule and oxidizing the adsorbing H 2 Ot hrough as trong coupling with the O-2 pp electrons.T he adsorbed OH species denotes ametallic feature and efficient electron transfer for easily deattaching from the surface (Figure 5b).…”
Section: Resultsmentioning
confidence: 99%
“…[162][163][164][165] Allerdings kçnnen nur wenige Heterostrukturen ¾nderungen der elektronischen Struktur herbeiführen und so die katalytische Effizienz durch Herabsetzung des Kontaktwiderstands steigern. Dieser Kontakt zwischen Halbleiter-u nd Lei-termaterialien wird als Mott-Schottky-Kontakt bezeichnet und kann zur Energiebandverzerrung der Grenzschicht sowie Ladungswanderung zwischen zwei Materialien führen.…”
Section: Heterostrukturunclassified
“…Dieser Kontakt zwischen Halbleiter-u nd Lei-termaterialien wird als Mott-Schottky-Kontakt bezeichnet und kann zur Energiebandverzerrung der Grenzschicht sowie Ladungswanderung zwischen zwei Materialien führen. [164] Da die Elektronenaffinitätv on MoB im Va kuum grçßer war als die von g-C 3 N 4 ,k onnten Elektronen von g-C 3 N 4 auf MoB überwechseln, und das elektronenangereicherte MoB konnte so HER effizienter katalysieren. Einer detaillierten Analyse zufolge sind zueinander passende Elektronenaffinitäten und Fermi-Niveaus der Materialien die Voraussetzung fürd ie Konstruktion eines effizienten Mott-Schottky-Elektrokatalysators.…”
Section: Heterostrukturunclassified
See 1 more Smart Citation
“…However, the scarcity and high cost of platinum are the major factors to impede its industrial‐scale implementation of massive H 2 production from water reduction. Hence, numerous nonnoble‐metal materials including transition metals, transition metal dichalcogenides, carbides, borides, nitrides, phosphides, and their derivatives have been extensively investigated. Recently, it has been demonstrated that transition metal oxides (TMOs) and TMOs coupling with metallic transition metals benefit HER under alkaline conditions …”
Section: Introductionmentioning
confidence: 99%